Hoof Care for Florida Horses: VM265, 9/2024 - Bearden, Jennifer G.; Justesen, Caitlin (EDIS, 2024)
Maintaining the health and integrity of the hoof structures is critical to the overall health of the horse. This publication is intended to help Florida horse owners care for their horses’ hooves. Written by Jennifer Bearden and Caitlin Justesen, and published by the UF College of Veterinary Medicine, UF/IFAS Extension, September 2024.